Cationic Solid Lipid Nanoparticles of Resveratrol for Hepatocellular Carcinoma Treatment: Systematic Optimization, in vitro Characterization and Preclinical Investigation - Mahfoozur Rahman; Waleed Hassan Almalki; Obaid Afzal; Abdulmalik Saleh Alfawaz Altamimi; Imran Kazmi; Fahad A. Al‐Abbasi; Hani Choudhry; Sattam Khulaif Alenezi; Md. Abul Barkat; Sarwar Beg; Vikas Kumar; Abdulsalam Alhalmi (2020)
The present study focuses on the development and evaluation of the resveratrol (RV)-loaded cationic solid lipid nanoparticles (RV-c-SLNs) for the management of hepatocellular carcinoma (HCC).Optimization of formulation was performed using factorial design, and further in vitro drug release, cytotoxicity, biodistribution, in vivo preclinical, and biochemical evaluation were carried out.The optimized formulation exhibited uniform size, homogeneous disparity, positive zeta potential, and stability over 12-week storage at 25°C/60% RH. The in vitro drug release and cytotoxicity study showed 60% drug release within the first 6 hours and comparatively higher cytotoxicity on HepG2 cell line by resveratrol-solid lipid nanoparticle (RV-SLN) as compared to the RV solution. In addition, an anticancer action and biodistribution study on a rat model of HCC showed significant reduction of tumor volume and higher accumulation in the tumor tissue from RV-c-SLN (P<0.01) over RV solution and RV-SLN. Furthermore, RV-c-SLN showed significant down-regulation in the levels of pro-inflammatory cytokines and balancing of antioxidant enzymes. Histopathological investigation showed reduced occurrence of hepatic nodules, necrosis formation, infiltration of inflammatory cells, blood vessels inflammation, and cell swelling.Overall, the obtained results construed that RV-c-SLN with improved antitumor activity as clearly evident from in vitro, in vivo, and biochemical investigations.